2006
DOI: 10.1126/science.1132998
|View full text |Cite
|
Sign up to set email alerts
|

RIG-I-Mediated Antiviral Responses to Single-Stranded RNA Bearing 5'-Phosphates

Abstract: Double-stranded RNA (dsRNA) produced during viral replication is believed to be the critical trigger for activation of antiviral immunity mediated by the RNA helicase enzymes retinoic acid-inducible gene I (RIG-I) and melanoma differentiation-associated gene 5 (MDA5). We showed that influenza A virus infection does not generate dsRNA and that RIG-I is activated by viral genomic single-stranded RNA (ssRNA) bearing 5'-phosphates. This is blocked by the influenza protein nonstructured protein 1 (NS1), which is fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

51
1,736
1
11

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 1,984 publications
(1,834 citation statements)
references
References 22 publications
51
1,736
1
11
Order By: Relevance
“…However, the replication of IAV ΔNS1, like that of parental wild‐type IAV, was similar in Ago2 −/− Mavs −/− MEFs reconstituted to display an intact or a defective RNAi pathway (Appendix Fig S7D). Finally, because IAV is a negative‐sense ssRNA virus and may not produce sufficient amounts of dsRNA (Pichlmair et al , 2006; Weber et al , 2006), we also tested a (+)ssRNA picornavirus, EMCV. As a precaution, we chose an EMCV mutant lacking the L gene, which encodes an IFN antagonist (Hato et al , 2007) that could potentially act as a VSR.…”
Section: Resultsmentioning
confidence: 99%
“…However, the replication of IAV ΔNS1, like that of parental wild‐type IAV, was similar in Ago2 −/− Mavs −/− MEFs reconstituted to display an intact or a defective RNAi pathway (Appendix Fig S7D). Finally, because IAV is a negative‐sense ssRNA virus and may not produce sufficient amounts of dsRNA (Pichlmair et al , 2006; Weber et al , 2006), we also tested a (+)ssRNA picornavirus, EMCV. As a precaution, we chose an EMCV mutant lacking the L gene, which encodes an IFN antagonist (Hato et al , 2007) that could potentially act as a VSR.…”
Section: Resultsmentioning
confidence: 99%
“…There is evidence to show that the RLRs are concomitantly upregulated and possibly play a contributory role in mediating the pro‐inflammatory cytokine responses 3, 7, 10, 15, 33. Although both RIG‐1 and MDA‐5 often showed upregulation in influenza and other respiratory viral infections, innate responses against influenza viruses are likely dependent on RIG‐1 and suppressible by the viral NS‐1 protein 7, 13, 26, 33…”
Section: Discussionmentioning
confidence: 99%
“…Recent in vitro and in vivo studies on influenza pathogenesis have shown that TLR activation induces expression of type I interferons and pro‐inflammatory cytokines (e.g., IL‐6, TNF‐α), limiting viral replication and dissemination, mediating tissue inflammation, and link to adaptive immunity development 3, 7, 8, 9, 10, 11, 123, 7, 10, 13. Recently, data from animal studies have further shown that targeting the TLRs (with agonists) may rapidly upregulate the innate immunity to provide broad‐range, virus strain non‐specific protection against lethal influenza challenge 4, 11, 14, 15, 16, 17.…”
Section: Introductionmentioning
confidence: 99%
“…Recognition of an RNA substrate by the C‐terminal domain (CTD) of RIG‐I or MDA5 leads to structural rearrangements that are transmitted via the conserved helicase domain and allow the two N‐terminal caspase activation and recruitment domains (CARDs) to trigger oligomerisation of the adaptor MAVS (mitochondrial antiviral signalling) on the mitochondrial membrane, which in turn leads to IRF‐3, IRF‐7 and NF‐κB activation, nuclear translocation and IFN gene transcription (Goubau et al , 2013; Wu & Chen, 2014; Sohn & Hur, 2016). Whilst RIG‐I recognises 5′di‐ or tri‐phosphates at the base‐paired extremities of viral RNA, MDA5 and LGP2 recognise long double‐stranded RNA (dsRNA), the precise features of which are less well‐defined (Hornung et al , 2006; Kato et al , 2006; Pichlmair et al , 2006, 2009; Goubau et al , 2014). LGP2 remains the most enigmatic member of the RLR family.…”
Section: Introductionmentioning
confidence: 99%